The English Country House and the English Country House Disturbed: comparing different aesthetic treatments of space in Jane Austen´s Pride and Prejudice and Ian McEwan´s Atonement - Strašková, Jana (Univerzita Pardubice, 2014)
This diploma thesis addresses different aesthetic treatments of space, especially the English country house in both Pride and Prejudice by Jane Austen and in Ian McEwan´s Atonement. The theory considered to be essential for this thesis is combined with excerpts taken from primary sources which serve as the cornerstone for literary analysis. Fundamental books for the theory are mainly of foreign origin such as Gaston Bachelard´s The Poetics of Space, Mark Girouard´s Life in the English Country House and Stuart Lowe´s Housing Policy Analysis. However, the thesis also considers the literary insights of Czech authors, for example Daniela Hodrova. This diploma thesis will provide readers with an extensive resumé in the Czech language. Finally, the author´s findings will be summarised in a relevant conclusion.
Keywords: Anglie; venkovské domy; poetika prostoru; Jane Austenová; Ian McEwan; literární analýza; England; country houses; poetics of space; Jane Austen; literary analysis